Multistability and Period-Adding in a Four-Dimensional Dynamical System with No Equilibrium Points - Daumann C.C.* (2021)
© 2021, The Author(s), under exclusive licence to Springer Nature India Private Limited.In this work we investigate the dynamics of a four-parameter four-dimensional nonlinear dynamical system with a hyperbolic cosine nonlinearity, and with no equilibrium points. A suitable cross-section of the four-dimensional parameter-space is used to characterize the occurrence of multistability in this system, as well as to observe the organization of chaos and periodicity. Cross-sections of basins of attraction of hidden chaotic and quasiperiodic coexisting attractors are reported.